The Effect of Service Quality on User Satisfaction with Perceived Usefulness as an Intervening Variable - Maryani, Maryani; Qomariah, Nurul; Martini, Ni Nyoman Putu; Sobirov, Bobur (Ilomata International Journal of Management, 2025)
The increasing demand for efficient and usercentered public services has led to the development of the J-KOPI (Jember Smart City) application. However, user satisfaction remains a challenge due to varying levels of perceived service quality and public trust. This study aims to analyze the impact of service quality on user satisfaction, with perceived usefulness as a mediating variable. Utilizing a descriptive quantitative approach, the study employs Structural Equation Modeling (SEM) to assess relationships between these variables. Data were gathered through observations, online questionnaires, and documentation, focusing on key indicators such as reliability, responsiveness, assurance, empathy, and trust dimensions. The results reveal that both service quality significantly influence user satisfaction directly and through perceived usefulness. Notably, service quality dimensions positively correlate with perceived usefulness, enhancing users' productivity and satisfaction. These findings suggest that strengthening both service quality is essential for improving user satisfaction and promoting broader adoption of J-KOPI, supporting Jember's smart city vision.